2019
DOI: 10.2478/msp-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of Cu on the properties of eutectic Sn-Bi solder alloy

Abstract: The present work reports the effect of Cu addition on the melting point, hardness and electrical resistivity of Sn-57 wt.% Bi eutectic solder alloy. Both binary eutectic Sn-57 wt.% Bi and ternary Sn-(57-x)Bi-xCu (x = 0.1, 0.3, 0.5, 0.7 and 1 wt.%) alloys containing various amounts of Cu were developed by melting casting route. The microstructure of the various solder alloys was analyzed using an optical microscope and a SEM. The variation in melting point, hardness and electrical resistivity of the Sn-Bi eutec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…% of Ni and Zn in Sn-58Bi solder resulted in 395 MPa (Yang et al, 2016b) and 750 MPa of Sn and 600 MPa of Bi (Zhou et al, 2018) There have been a few studies on the hardness of Sn-Bi alloys containing the same alloying element, but at different weight percentages. Alam et al (2019) reported that alloying Cu in Sn-57Bi increased the microhardness value linearly in proportion to the increase in wt. % of copper from 0.1 to 1.0.…”
Section: Hardnessmentioning
confidence: 99%
See 4 more Smart Citations
“…% of Ni and Zn in Sn-58Bi solder resulted in 395 MPa (Yang et al, 2016b) and 750 MPa of Sn and 600 MPa of Bi (Zhou et al, 2018) There have been a few studies on the hardness of Sn-Bi alloys containing the same alloying element, but at different weight percentages. Alam et al (2019) reported that alloying Cu in Sn-57Bi increased the microhardness value linearly in proportion to the increase in wt. % of copper from 0.1 to 1.0.…”
Section: Hardnessmentioning
confidence: 99%
“…The hardness values of Sn-Bi solder systems alloyed with 0.5 wt. % of Ni (Yang et al , 2016b), Cu (Jayesh and Elias, 2020; Alam et al , 2019) and Al (Yang et al , 2019b) were studied. All studies used the same solder preparation technique except Alam, S. N. et al , and Yang, L. et al stated that the presence of 0.5 wt.…”
Section: Hardnessmentioning
confidence: 99%
See 3 more Smart Citations